Pemanfaatan zat aktif fitogenik sebagai modulator fermentasi rumen dan metabolisme pasca rumen pada ternak ruminansia - Syafiradewi Yulianti; U.Hidayat Tanuwiria; Yulianri Rizki Yanza (Fakultas Pertanian Universitas Majalengka, 2026)
Ruminant livestock productivity is substantially influenced by the efficiency of rumen fermentation and post-ruminal nutrient metabolism. The increasing restriction on antibiotic use as growth promoters has driven intensive research into plant-derived bioactive compounds, commonly referred to as phytogenic feed additives (PFAs), as alternative modulators of digestive physiology. This review aims to critically examine the scientific evidence on the role of phytogenic active substances, particularly tannins, saponins, and essential oils, in modulating rumen fermentation processes and post-ruminal metabolic pathways in ruminants. A systematic literature search was conducted using Scopus, ScienceDirect, SpringerLink, Wiley Online Library, and Google Scholar, employing keywords such as